1987
DOI: 10.1145/22719.24067
|View full text |Cite
|
Sign up to set email alerts
|

DIB—a distributed implementation of backtracking

Abstract: DIB is a general-purpose package that allows a wide range of applications such as recursive backtrack, branch and bound, and alpha-beta search to be implemented on a multicomputer. It is very easy to use. The application program needs to specify only the root of the recursion tree, the computation to be performed at each node, and how to generate children at each node. In addition, the application program may optionally specify how to synthesize values of tree nodes from their children's values and how to diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(65 citation statements)
references
References 18 publications
0
65
0
Order By: Relevance
“…First, to lower communication costs, we would like to steal large amounts of work, and in a tree-structured computation, shallow threads are likely to spawn more work than deep ones. This heuristic notion is the justification cited by earlier researchers [8,15,21,35,43] who proposed stealing work that is shallow in the spawn tree. We cannot, however, prove that shallow threads are more likely to spawn work than deep ones.…”
Section: The Cilk Work-stealing Schedulermentioning
confidence: 95%
See 2 more Smart Citations
“…First, to lower communication costs, we would like to steal large amounts of work, and in a tree-structured computation, shallow threads are likely to spawn more work than deep ones. This heuristic notion is the justification cited by earlier researchers [8,15,21,35,43] who proposed stealing work that is shallow in the spawn tree. We cannot, however, prove that shallow threads are more likely to spawn work than deep ones.…”
Section: The Cilk Work-stealing Schedulermentioning
confidence: 95%
“…Cilk' s scheduler uses the technique of work stealing [4,8,14,15,16,21,29,30,31,37,43] in which a processor (the thief) who runs out of work selects another processor (the victim) from whom to steal work, and then steals the shallowest ready thread in the victim's spawn tree. Cilk' s strategy is for thieves to choose victims at random [4,29,40].…”
Section: The Cilk Work-stealing Schedulermentioning
confidence: 99%
See 1 more Smart Citation
“…This process continues until all processors go idle or a solution is found. Finkel and Manber (1987) have presented the performance results of PDFS for a number of problems such as traveling salesman problem and other problems. Monien and Vornberger (1987) showed that a linear speedup can be obtained to solve combinatorial problems using parallelism.…”
Section: Related Workmentioning
confidence: 99%
“…In the DIB system [11], processors redo work of other processors even if no crash has been detected. Redoing occurs while a processor waits for its steal request being granted.…”
Section: Related Workmentioning
confidence: 99%